2016
DOI: 10.1159/000446641
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Cytokeratin 19-Expressing Cholangiocarcinoma-Like Tumour in a Liver Metastatic Lesion of Rectal Neuroendocrine Tumour

Abstract: Introduction: Tumours with adenocarcinoma and neuroendocrine components have often been reported, although the reason underlying the dual components remains unclear. Case Presentation: A 43-year-old woman with multiple liver metastatic lesions of rectal neuroendocrine tumour underwent primary tumour resection and subsequent liver transplantation. Pathological examination indicated a cholangiocarcinoma-like tumour with gland formation, adjacent to a liver metastatic lesion of the neuroendocrine tumour. This tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This is an important point that must be taken into account when evaluating these results, as a longer waiting time could have a major impact in dropping out from the LT list due to the progression of the disease. In countries with a long LT waiting time, such as the UK where the median time is 152 days [40], it could be difficult to add a new transplantable disease, as this, would inherently cause longer waiting time or even drop-out for other patients. In addition, the severe dearth of organs and mortality in the waiting list represent further problems.…”
Section: Strategies For Organs Allocation and Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important point that must be taken into account when evaluating these results, as a longer waiting time could have a major impact in dropping out from the LT list due to the progression of the disease. In countries with a long LT waiting time, such as the UK where the median time is 152 days [40], it could be difficult to add a new transplantable disease, as this, would inherently cause longer waiting time or even drop-out for other patients. In addition, the severe dearth of organs and mortality in the waiting list represent further problems.…”
Section: Strategies For Organs Allocation and Ethical Considerationsmentioning
confidence: 99%
“…In addition, the severe dearth of organs and mortality in the waiting list represent further problems. In the UK, the burden of waiting list mortality raises major ethical considerations, since it has been reported that the number of patients who die on the waiting list relative to the total number of LT is about 16% [40]. In this regard, recipients with metastatic liver disease usually have normal liver function.…”
Section: Strategies For Organs Allocation and Ethical Considerationsmentioning
confidence: 99%